Theatre of Enforcement at Sea: The Global Fight Against `Illegal Fishing' and the Criminalisation of Fisher Peoples and Exploitation of Fish Workers - Paula Satizábal; Gina Noriega-Narváez; Lina~M. Saavedra-Díaz; Philippe Le~Billon (Journal of Agrarian Change, 2025)
Illegal, unreported and unregulated (IUU) fishing has been internationally branded as a major threat to oceans. Frequently depicted as having profound societal impacts and operational synergies with other forms of criminal activities, which justify the need for a so-called global fight against IUU fishing to protect the marine commons and secure marine spaces. Whereas industrial fishing is the prime culprit, policy reforms are being promoted to regulate and formalise artisanal and traditional fishing practices. This raises questions on how enforcement and formalisation processes are translated into practice and shaped by economic interests within and beyond the oceans. In this intervention, we focus on the governance of IUU fishing in Colombia and anchor our critique into two acts—the act of criminalisation and the act of impunity —to uncover a theatre of enforcement at sea. We argue that the punitive approach to IUU fishing criminalises fisher peoples, whereas domestic, foreign and transnational capitalist actors continue to operate, depleting oceans and exploiting fish workers' labour with very limited control. We conclude by asserting that the fight against IUU fishing is in part a fight against precarious fish workers and fisher peoples, rather than against `ocean grabbers', reflecting biased criminalisation processes with differentiated impacts at the intersections of class, gender and race.
Keywords: 630; Colombia; criminalisation; illegal; unreported and unregulated fishing; marine conservation; marine governance; militarisation; political economy